North Atlantic Sub‐Polar Gyre Climate Index: A New Approach. Issue 6 (24th June 2019) - Biri, Stavroula; Klein, Birgit
Abstract: As decadal predictions become operational, the need to use, understand, and extract information from them becomes essential. A climate index is a simple diagnostic quantity that can be used to characterize integral aspects of a geophysical system such as circulation patterns, and thus can be used to evaluate decadal forecasts. One of the most studied and well documented regions of the World Ocean is the North Atlantic. The North Atlantic subpolar gyre is an important region for the modulation of European climate and where skillful predictions of up to a decade can be obtained. Ocean re‐analysis (ORA‐S4) data from 1959 to 2017 are used to introduce a new methodology to compute a climate index of the North Atlantic subpolar gyre that captures both the variability in its strength and shape, the latter was to our knowledge never investigated previously as part of the variability of the gyre on interannual to decadal time scales. The methodology reveals two states of the gyre (before and after 2000), the former is mainly driven by temperature and the latter by a combination of mechanisms that interact to sustain a relatively stable subpolar gyre in terms of strength. Plain Language Summary: Decadal predictions is a relatively new topic in climate science and is driven by the needs of industry and society to adapt to future climate states. To that end, elaborate earth system models provide forecasts that nevertheless need to be validated. Some regions of the world ocean are easier to predict such as the North Atlantic subpolar gyre. One way to validate the forecasts is through climate indeces. To that extent, we follow a new approach to define a climate index for the subpolar gyre that captures many features of the circulation that relate to the strength and the size of the gyre. Key Points: A climate index that is a measure of the changes in strength and in the shape of the North Atlantic subpolar gyre system The suggested methodology can be applied to various data sets and can be improved with data sets with higher spatial resolution The climate index distinguishes periods with different dynamical characteristics before and after 2000